Growth Response of Sugarcane Seedlings (Saccharum officinarum L. cv. Kidang Kencana) to NPK Fertilizer Doses and Gibberellin Application in Bud-Based Seedling - Novitasari, Adin; Satriyono, Wahono; Sudiarso, Sudiarso; Muharram, Muhammad (CV. Komunitas Dunia Peternakan, 2026)
Sugarcane cultivation often faces productivity losses due to poor sprouting and non-uniform initial growth. In bud-based nursery systems, seedling quality is heavily constrained by limited media volume and low buffering capacity. This study aimed to evaluate the synergistic effects of NPK fertilizer dosages and Gibberellic Acid (GA) concentrations on the growth and physiological vigor of sugarcane seedlings. The experiment was conducted using a Completely Randomized Design featuring nine treatment combinations with four replications. Parameters measured included plant height, stem diameter, the number of tillers, the number of leaves, and the chlorophyll index. The results demonstrated that the application of the NPK 150 kg ha⁻¹ + GA 50 ppm treatment significantly enhanced plant height, stem diameter, number of shoots, and the number of leaves compared to the control treatment. Statistical analysis revealed a significant interaction between nutrient availability and hormonal stimulation in overcoming the constraints of limited rooting environments. These findings suggest that precise integration of chemical fertilization and exogenous growth regulators is essential for producing high-quality planting material, potentially reducing losses in the subsequent planting cycle. In the future, it is necessary to confirm the use of a combination of NPK fertilizer with gibberellin during the vegetative period of plants so that the information obtained is comprehensive.